SKRINING FITOKIMIA EKSTRAK ETANOL 70% DAUN GANYONG MERAH (CANNA EDULIS KERR.) - Supriyanto; Endra Pujiastut; Maulina Nur (Joseph: Journal of Science and Pharmacy, 2021)
Background: Canna (Canna edulis Kerr) is a type of tuber which   is a clumped herbaceous plant. N-Hexan Extract of red and white   Cannabis contains alkaloids, steroids, flavonoids, and phenolics.   Purpose: to determine the class of compounds contained in the 70% ethanol extract of Red Ganyong Leaves. Method: This research was carried out in the process of making powder. After the powder was obtained by maceration using 70% ethanol to obtain a thick extract. This viscous extract was then identified in the class of flavonoid compounds, alkaloids, steroids, phenolics, tannins and saponins. Results: The drying results obtained were yielded extracts. The phytochemical screening results showed that the flavonoids, steroids, phenolic, tannin and saponin groups were negative, while the results were negative for the alkaloids.   Conclusion: The 70% ethanol extract of red Ganyong leaves contains flavonoids, steroids, phenols, tannins and saponins